Literature Review: Kecemasan dengan Activity Daily Living pada Penderita Diabetes Melitus - Singal, Yesi Yosua; Kundre, Rina Margaretha; Masi, Gresty Natalia Maria (Mapalus Nursing Science Journal, 2025)
Background: Diabetes mellitus is a metabolic disease that occurs due to impaired insulin action, impaired insulin secretion, or both. In addition to physical effects, people with diabetes mellitus tend to suffer from psychological effects such as anxiety. Psychological and physical health problems result in disability that leads to dependence on other people and sufferers need help in fulfilling their daily living activity. The purpose of this study was to analyze Anxiety and Daily Living Activity in Diabetes Mellitus sufferers with the Literature Review The method used to compile this literature review was to search through an electronic database. The article search was carried out using the keywords Anxiety, Activity dalily living, diabetes Mellitus which was traced through Google Scholar and Pubmed 1934 articles were found, only 15 articles were eligible. Result Based on the articles that have been reviewed, it shows that anxiety and activity daily living greatly affect people with diabetes mellitus, patients with anxiety and poor activity daily living independence experience abnormal blood sugar levels and even affect quality of life and increase the risk of complications and disability. Conclusion from the fifteen articles it was found that there is a relationship between anxiety and activity daily living in people with diabetes mellitus. Keywords: Anxiety, Activity Daily Living, Diabetes Mellitus.